A mannose receptor is involved in the anti-Vibrio defense of red swamp crayfish. Issue 82 (November 2018) - Man, Xin; Pan, Xin-Tong; Zhang, Hong-Wei; Wang, Yue; Li, Xin-Cang; Zhang, Xiao-Wen
Abstract: Mannose receptor (MR), a member of pattern-recognition receptors (PRRs), is the first MR family member to be discovered that plays a critical role in immunity. The function of MRs has been reported in mammals and teleosts while none in invertebrates. In the present study, we identified a MR-like gene (designated as PcMR ) from red swamp crayfish, Procambarus clarkii . The PcMR cDNA is 6848 bp long with a 6288 bp open reading frame that encodes a polypeptide with 2095 amino acid residues. PcMR transcripts were mainly detected in hepatopancreas and hemocytes, and upregulated by Vibrio anguillarum challenge. The Pc MR protein contained 14 C-type lectin domains (CTLDs) and they were divided into four fragments ( CTLD 1–3, CTLD 4–6, CTLD 7–10, CTLD 11–14 ). The four recombinant proteins encoded by the four fragments were all expressed and purified. Microorganism-binding and sugar-binding assay showed that CTLD 1–3, CTLD 4–6, CTLD 7–10, CTLD 11–14 could bind to a variety of bacteria, as well as glycoconjugates on the bacterial surface. Moreover, they agglutinated bacteria in a calcium-dependent manner. Bacteria clearance experiment manifested that the mixed proteins facilitated the clearance of injected bacteria in crayfish. PcMR silencing by siRNA interference impaired the bacterial clearance ability. These results suggest Pc MR is involved in the antibacterial defense of crayfish, and this study will help us better understand the functions of invertebrate MRs. Highlights: The mannose receptor in Procambarus clarkii (PcMR) is a transmembrane protein with 14 C-type lectin domains (CTLDs). PcMR shows microorganism-binding, sugar-binding, microorganism-agglutinating and opsonin activities. First functional analyses of mannose receptor in invertebrates.